Biogas production from co-digestion of corn stover and chicken manure under anaerobic wet, hemi-solid, and solid state conditions - Li, Yeqing; Zhang, Ruihong; Chen, Chang; Liu, Guangqing; He, Yanfeng; Liu, Xiaoying (Bioresource technology, 2013)
•Synergistic effects were found in CS:CM ratios of 3:1 and 1:1.•In W-AD and HSS-AD, highest methane yields were obtained at CS:CM ratio of 3:1.•Highest volumetric productivity of 14.2L/L was found in SS-AD at CS:CM of 1:1.•VFA/TA value of 0.4 was a more important criterion than NH3-N or FA concentration. Corn stover (CS) and chicken manure (CM) are ubiquitous agricultural wastes at low cost and have the potential to achieve a nutrient-balance when mixed together to produce biomethane via anaerobic digestion (AD). The main objective of this work was to investigate methane production at different CS to CM ratios and to evaluate the process stability under wet (W-AD), hemi-solid state (HSS-AD) and solid state (SS-AD) conditions. Results showed that synergistic effects were found when mixing two substrates at CS:CM ratios of 3:1 and 1:1 (on volatile solid basis). The highest methane yield of 218.8mL/g VSadded was achieved in W-AD at CS:CM ratio of 3:1. In SS-AD, the highest volumetric methane productivity of 14.2Lmethane/Lreactor volume was found at CS:CM of 1:1. The results of this work provide useful information to improve the efficiency and stability of co-digestion of CS and CM under different AD conditions.